Media elite attitudes towards new media ethics: A field study - Alsubhi, Reemah Hamed (Journal of Humanities & Social Sciences, 2021)
The study sought to identify the understanding and understanding of media elites with concepts of media ethics New and their attitudes towards it through their practice of applied media work. This study aims to: A number of objectives were to identify the awareness of the media elite and the media establishment and its employees with the concept of new media ethics and the media code of ethics and their commitment to it, and identifying the obstacles to applying new media ethics on the website and accounts Social communication for the media organization. The study adopted the descriptive approach, through Survey of ethical practices in the media profession for workers in the new media and the most important conclusion Professional ethics to be based on. A survey of the ethical aspects of charters Media honor in the framework of social responsibility theory ‏The study used the questionnaire tool Collecting information from the study sample that consisted of (292) male media elites and females. The researcher reached a number of important results as follows: Most of the media elite They support the commitment of the media to sign a professional code of honor, and (58%) of the media elite They affirm the commitment of their media organization to the ethics of media work and (40%) affirm their commitment Workers with ethics in media work, and (55%) of the media elite were subjected to being prevented from publishing media material.‏The study recommended the necessity to define and accurately classify the code of ethics for media professionals The necessity to work according to the requirements of media ethics, and to monitor and control new media in accordance with The specified standards, and recommends the necessity of respecting the foundations of Saudi culture; Because the media arises and develops in Frame of reference for the country in which it appears.